Tantangan dan Peluang Pembelajaran Bahasa Arab di Era Digital - Vivi Sutinalvi; Annisa Harahap; M.Yusri Ali Lubis; Sahkholid Nasution (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
Learning Arabic in the digital era faces great challenges and opportunities. The main challenges include limited technological infrastructure, low skills of educators in utilizing technology, and limited internet access, especially in remote areas. Additionally, technical issues such as the use of Arabic letters and the distraction of non-educational content affect learning effectiveness. The quality of digital learning materials also needs to be improved to make them more interactive. On the other hand, technology provides opportunities such as flexible access to learning resources, gamification to increase motivation, as well as more personalized and multimedia-based learning. Digital learning allows wider access to education, especially for students in remote areas. To maximize this potential, training for educators, improving infrastructure and developing quality content is needed. Policy support and collaboration between government, educators and technology developers are very important to optimize Arabic language learning in the digital era.